Exploring the scope of 4sb and 12a lymph node dissection for cT2-4 lower third gastric cancer: Study protocol for a prospective cohort trial - Zhang, Haiqiao; Zheng, Zhi; Liu, Xiaoye; Cai, Jun; Yin, Jie; Zhang, Jun (Frontiers in Surgery, 2022)
Background Currently, the extent of 4sb and 12a lymph node dissection is not clear and is based on the personal understanding of the surgeon. It may result in damage to the splenic artery and portal vein, leading to surgical complications. Therefore, this study aims to explore the scope of 4sb and 12a lymph node dissection in cT2-4 lower third gastric cancer. Methods This is an ongoing prospective cohort trial. The total sample size required for the trial (March 2022 to February 2025) is approximately 524 patients. The participants are divided into the experimental (4sb first branch and 12a anterior lymphadenectomy) or control groups (traditional 4sb and 12a lymphadenectomy). Electronic data capture systems will be used to collect demographic, laboratory test, auxiliary examination, operation, postoperative condition, postoperative pathology, and follow-up data. The primary outcome is the 12a lymph node metastatic rate. Secondary outcomes include the pathology (consisting of the 4sb lymph node metastatic rate, the number of 4sb lymph nodes dissected, the number of 12a lymph nodes dissected and tumor pathological staging), a safety evaluation index (consisting of complications and mortality ≤30 days after surgery), an efficacy evaluation (consisting of operation data and postoperative recovery status), and follow-up data (consisting of 3-year or 5-year disease-free survival and overall survival). Discussion By exploring the scope of 4sb and 12a lymph node dissection on the premise of ensuring radical cure of the tumor, the operation is simplified, the operation time is shortened, the damage of important blood vessels is reduced, the intraoperative and postoperative complications are reduced, and the patient recovers as soon as possible. Our study is a prospective exploration of the pathology, safety, efficacy, and prognosis of the new and traditional methods of 4sb and 12a lymph node dissection. Trial registration Chinese Clinical Trial Registry, ChiCTR2200057698 (registration date: March 15, 2022).